Sistem Monitoring Sepeda Motor Berbasis Mikrokontroler Menggunakan GPS - Endo Army Siddiq; Hansi Effendi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Currently, the number of vehicle thefts in the city of Padang is still high. it is very difficult to track the vehicle because there are too many vehicles in the city of Padang. This study aims to design and build a vehicle tracking system using the sim808 module, relay and Arduino Uno. testing by measuring the accuracy in locking satellite signals and measuring the length of time required for vehicle tracking devices to receive and send short messages in the form of information on the user's vehicle position and disconnect the motorcycle's electrical system. has successfully designed a vehicle tracking device using the sim808 and Arduino module with the value as a support to make the motorbike turn off and make a sound so that it can easily find the location of the user's vehicle.